Mapping the Research on Corporate Governance in Sensitive Industries - Andreea Madalina Bojan; Camelia Iuliana Lungu; Chirata Caraiani (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- Which are the trends and the impact in the research area covering corporate governance in sensitive industries? Motivation- The research enhances prior literature on corporate governance under specific risk, uncertainty and socio-economic conditions. The referenced topics and timeframe highlight the focus on sensitive industries as a challenge, considering the mixed effects of crises conditions. Idea- This paper creates a comprehensive overview on the corporate governance in sensitive industries research landscape, considered under universalist, social constructivist, and presentation perspectives. Data- Information on publication trend, papers' main characteristics, academic collaboration, and factors with significant influence on times cited are collected for a sample of 926 scientific publications from the Web of Science database. Tools- The network visualization for co-authorship and co-occurrence of keywords is based on using VOSviewer software, while statistical and econometric analysis of the database is performed using SPSS Statistics V.23. Findings- The results emphasize that most of the papers are published in leading journals, while 2022 is the year that stands out with the highest number of publications. From the perspective of the business field, the research focus is on Banking, Energy, Logistic, Pharmaceutical, and Tourism industries. Muchmore, statistical analysis demonstrates that there is a significant difference between the types of publications. Regression analysis shows that times cited are positively and statistically significant correlated with cited reference count and article age. Contribution- This study may be of great interest to academic and business environments. It summarizes information for a specific topic, whose evolution managers and practitioners are interested in. Furthermore, it fills the gap in examining the research impact based on several characteristics that exert an influence on times cited, contributing to the body of knowledge regarding the classification of research features under the universalist, social constructivist, and presentation perspectives.
Keywords: M41; G34; 650; corporate governance; sensitive industries; network analysis; regression analysis